Isolation, diagnosis, and antibiotic resistance of the plant pathogen Erwinia tracheiphila (NTU Journal of Agriculture and Veterinary Science, 2024)
This study was conducted with the aim of identifying the cause of bacterial wilt disease in cucurbits, which is considered one of the most threatening diseases for melon and cucumber production because it causes great losses that can reach up to 75% of the annual production, and the study proved that Erwinia tracheiphila is the main cause of this disease after isolating (50) isolates of it from waterm melons and cucumbers leaves that showed symptoms of infection and performing several chemical tests to diagnose it. The effect of (6) different types of antibiotics (rifampin, cefotazima, piperacillin, ceftriaxone, tobramycin and ciprofloxacin) on it was studied by the sensitivity test method. The antibiotic ciprofloxacin gave the highest inhibition value, as indicated by the diameter of the inhibition zone around the disc, which reached (35) mm, followed by tobramycin (20) mm and piperacillin (15) mm, while other antibiotics were ineffective due to resistance. This result indicates that this bacterium is resistant to several drugs, but at the same time it can be treated with antibiotics. That they are sensitive to them, which was indicated in this study for the purpose of controlling its infection of plants, especially cucurbits. The results of this study are therefore very important in terms of promoting the overcoming of its natural resistance to many antibiotics, which limits the possibility of controlling it when resistant strains appear in a particular country.